The encyclopedic sourcebook of Satanism - Lewis, James R.; Petersen, Jesper Aagaard (Prometheus Books, 2008)
Modern Satanism -- Satanic ritual abuse as a moral panic -- Satanic ritual abuse as demonology -- Satanism and the media -- Satanism and crime